2011
DOI: 10.3892/ijo.2010.890
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits a large panel of kinases implicated in cancer cell biology

Abstract: Abstract. Flavonoids are polyphenolic secondary metabolites from plants that possess a common phenylbenzopyrone structure (C6-C3-C6). Depending upon variations in their heterocyclic C-ring, flavonoids are categorised into one of the following groups: flavones, flavonols, flavanones, flavanols, anthocyanidins, isoflavones or chalcones. Flavonols include, among others, the molecules quercetin, myricetin and kaempferol. The anticancer activity of flavonols was first attributed to their electron-donating ability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
(108 reference statements)
0
34
0
Order By: Relevance
“…Our findings suggest that inhibition of PIM1 kinase may have a role in regulating lymphocyte proliferation in CLL/SLL. However, as quercetin is known to inhibit many kinases in vitro [4], it is possible that the inhibitory effects on lymphocytes demonstrated here may be attributable to kinases other than, or in addition to, the PIM1 kinase.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings suggest that inhibition of PIM1 kinase may have a role in regulating lymphocyte proliferation in CLL/SLL. However, as quercetin is known to inhibit many kinases in vitro [4], it is possible that the inhibitory effects on lymphocytes demonstrated here may be attributable to kinases other than, or in addition to, the PIM1 kinase.…”
Section: Discussionmentioning
confidence: 92%
“…Quercetin (3,3′,4′,5,7-pentahydroxyflavone) is a flavonoid naturally occurring in fruits and vegetables [3] and is commercially available for human use as a dietary supplement. It is known to inhibit many kinases, including PIM1 (∼95% inhibition in cell culture) and is cytostatic rather than cytotoxic [4]. It was administered in a phase I clinical trial to 51 patients with cancer not amenable to standard therapies in 1996 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phosphodiesterases (PDEs) were suggested to be affected by quercetin [94], as well as topoisomerases I and II [95] and Mcl-1 [86]. Most importantly, quercetin was identified as a broad-spectrum kinase inhibitor [96, 97]. Has all this knowledge been translated into therapy or prevention?…”
Section: Plant-derived Compounds Tested In Clinical Trialsmentioning
confidence: 99%
“…Moreover, vitamin E supplementation was found to counteract the beneficial effects of exercise by preventing the induction of aortic catalase activity and endothelial NO synthase expression [23]. Flavonoids are a class of naturally occurring compounds widely present in fruits, vegetables and beverages derived from plants that have known antioxidant activity [24,25]. One such flavonoid, quercetin, has been shown to be an effective free-radical scavenger that inhibits lipoprotein oxidation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also suggested that quercetin possesses anti-inflammatory properties as well as antioxidant activity. As an antioxidant and anti-inflammatory, quercetin appears to alleviate oxidative stress via diverse pathways, including NF-κB dependent mechanism [25], decrease activity of JAK3 [26], and/or by blocking the activation of pro-inflammatory/oxidative stress mediator signal transduction [27]. Quercetin has also been shown to prevent the accumulation of fat in the liver of mice fed a high fat diet [28] and to lower blood lipids in people with dyslipidemia [29].…”
Section: Introductionmentioning
confidence: 99%